Laparoscopic total colectomy for ulcerative colitis after liver transplantation is feasible - Darnis, Benjamin (J Minim Access Surg, 2017)
Ulcero-haemorrhagic rectocolitis can occur after liver transplantation for sclerosing cholangitis. Total colectomy with or without proctectomy may be indicated in case of chronic drug-resistant colitis, dysplasia or cancer. Today, laparoscopic approach is the standard for such procedure in non-operated patients. We performed a completely laparoscopic total colectomy 5 years after a liver transplantation. There were a few peritoneal adherences, and we could safely perform the procedure almost as usual. It provided all the advantages of the laparoscopic approach in the post-operative course.